Prevalence of human papillomavirus in laryngeal and hypopharyngeal squamous cell carcinomas in northern Spain. Issue 1 (February 2015) - Rodrigo, Juan P.; Hermsen, Mario A.; Fresno, Manuel F.; Brakenhoff, Ruud H.; García-Velasco, Fabian; Snijders, Peter J.F.; Heideman, Daniëlle A.M.; García-Pedrero, Juana M.
Highlights The significance of HPV in the etiology of non-oropharyngeal head and neck cancers is uncertain. We analyzed the possible association of HPV infection with laryngeal and hypopharyngeal cancers. Only two cases (1.6%) were found positive for HPV; both contained HPV type 16. The proportion of laryngeal and hypopharyngeal cancers attributable to HPV seems to be very low.